Strategi World Wide Fund For Nature dalam Menekan Perdagangan Ilegal Satwa Liar di Indonesia Tahun 2018 - Muhammad Fadel Narendra; Mahdi, Imam (Universitas Muhammadiyah Sorong, 2025)
This research discusses WWF's strategy in suppressing illegal wildlife trade in Indonesia in 2018. Indonesia occupies the highest position regarding illegal wildlife trade cases compared to other countries in the world, especially in the 2015-2017 period. WWF considers this problem to be a serious phenomenon that must be resolved through concrete actions. In 2018, WWF launched the “Stop! Illegal Trade in Wild Animals,